Como incide el baloncesto en el desarrollo de la expresión corporal - Chariguamán Morocho, Vinicio Paúl (2016)
The world today is characterized by a hasty progress at all levels and especially in the area of Physical Culture, since the development of modern life leads in many cases to a sedentary lifestyle is also proven that through this course you can practice exercises achieve optimum progress in body language. That is why the physical activity is a priority need today..In educational institutions especially in the Education Unit "Hermano Miguel" in the fourth year of basic general education; where by the project seeks to prioritize everything related to the formation and development of communication skills and habits to improve the physical expression of students, having a direct influence on the formation of values and ideological chord political convictions with the environment in which we live, the use of games as a means to develop body expression through basketball. Teachers should focus their efforts on developing methodological class of physical education for students as much as possible through active work assimilate the importance of this subject in the development of his life. We must recognize that this student stage play activities no longer have the level of importance it deserves to follow an increasingly specific treatment in the development of content, both physical condition, with a clear orientation towards health, as specific skills, where games and sports, motor skills, activities in the natural environment and activities of rhythm and expression are included.